APPLICATION OF FACTOR ANALYSIS IS IN MARKET OF LABOUR RESEARCH FRONTIER REGION (ON EXAMPLE OF VOLYN AREA) - Пасевич, Юрій (Human Geography Journal, 2014)
In the article, on the basis of the generalized and systematized statistical information, the factor analysis of factors of labour-market of the Volyn area is carried out. Certainly and the quality signs of basic factors are analysed that influence to the market of labour of region. Territorial differences and features of degree of display of factors of labour-market are educed and reasonable. Classification of administrative districts and cities of area is conducted on a degree and specific of display of factors. Mapping of the got results of research is carried out.